Knowledge,attitude and utilization of insecticide treated nets among caretakers in malaria prevention in underfive children (Mansa.) - Chizuni,Callen (Lusaka: University of Zambia , School of Medicine, 2010)
The main aim of the study was to determine knowledge,attitude and utilisation of insecticide treated nets among caretakers in malaria prevention in underfive children. The major hypothesis of the study was "there is an association between level of knowledge on insecticide treated nets-ITNs and utilization of ITNs".
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: public health --mansa --zambia.; malaria prevention --mansa --zambia.